Seasonal variation of currents in the Cam-Nam Trieu estuary (Hai Phong, Vietnam): results from a 3D modelling - Nguyen, Thanh Duong; Nguyen, Minh Hai; To, Thi Lan Phuong; Vinh, Vu Duy (Vietnam Journal of Marine Science and Technology, 2025)
This paper employs the Delft3D numerical model to characterize the seasonal variation of currents in the Cam-Nam Trieu estuary during 2015. Model outputs were validated and calibrated against measured water level and current velocity data at Hon Dau. The convincing performance of Delft3D in replicating natural conditions is evident from the high Nash-Sutcliffe Efficiency (NSE) (up to 0.972), low Root Mean Squared Error (RMSE), and strong R-squared (R) values for both water level and current velocity. Current magnitudes in the wet and early wet seasons significantly exceed those observed during the dry season. Peak ebb tide velocities can reach 1.6 m/s. While river discharge to the sea is diminished in the dry season, the impact of tides becomes more pronounced, with a clearer stratification of water velocity during spring tides compared to neap tides. The influence of strong river flow in the dry season is apparent in higher current velocities during ebb and low tides relative to flood and high tides, particularly during neap tide conditions. The successful replication of the Cam-Nam Trieu estuary’s hydrological regime by the Delft3D model positions it as a valuable tool for future predictive simulations in the region. These simulations will make substantial contributions to coastal and marine management. The findings of this research serve as a foundational reference for subsequent studies.